Assessing financial protection against disasters a guidance note on conducting a disaster risk finance diagnostic. (Asian Development Bank, 2017)
Disaster risk finance aims to improve the ability of governments to clarify and meet obligations arising from shocks caused by disasters while minimizing threats to development progress and fiscal stability. Increasingly, governments seek to meet this objective and manage the financial impact of disasters triggered by natural hazards in a comprehensive and strategic way.